Synthesis and characterization of hydrochars produced by hydrothermal carbonization of oil palm shell - Nizamuddin, S.; Jaya Kumar, N.; Sahu, J.; Ganesan, P.; Mujawar, Mubarak; Mazari, S. (Wiley-Blackwell Publishing, 2015)
In this paper, hydrothermal carbonization (HTC) is applied to oil palm shells to produce a solid fuel known as hydrochar. The effect of reaction temperatures 220–290 °C at reaction time 30 min, and a biomass to water ratio of 0.15 g/g (15 wt %) was investigated for synthesis of hydrochar. The hydrochar yield percentage decreased from 62.4 to 43 % with increasing temperature from 220 to 290 °C. In addition, carbon percentage increased with an increase in temperature from 26.93 (oil palm shell) to 63.77 % (hydrochar produced at 290 °C). The higher heating value (HHV) tended to increase from 12.24 MJ/kg (oil palm shell) to 26.80 MJ/kg for hydrochar products. The raw palm shell and hydrochars were characterized using Fourier Transform Infrared (FTIR), Branuer‐Emmett‐Teller (BET), Field Emission Electron Microscopy (FESEM), and thermogravimetric analysis (TGA). Surface porosity of hydrochar product increased, which resulted in a compacted surface and large surface area. BET surface area, total pore volume, and average pore diameter were improved from 0.316 m2/g, 0.001 29 cm3/g, and 45.1153 nm to 12.5996 m2/g, 0.0557 cm3/g, and 113.4120 nm, respectively, at 260 °C.